COEFICIENTE DE PERFORMANCE DOS FUNDAMENTOS DO VOLEIBOL DE UMA EQUIPE FEMININA SUB 15: UM ESTUDO NO CAMPEONATO DO PARANÁ DE 2015 - Marques Junior, Nelson Kautzner; Arruda, Danilo (Revista Observatorio del Deporte, 2015)
The objective of the study was to determine the performance coefficient (PC) of the skills of a female team under 15 during the championship realized in the Paraná state in the year 2015. The subjects of the study were composed by a female team under 15 that played the Curitiba Cup and the 1st Phase of the Paraná Championship. The 10 games of this team were filmed far later analysis with a scout elaborate in the Excel® 2013. The Kruskal Wallis Anova detected significant difference of the PC of the pass (H 9 = 38,50, p = 0,0001), of the set (H 9 = 73,06, p = 0,0001), of the attack (H 9 = 31, p = 0,0003) and of the defense (H 9 = 28,44, p = 0,0008) of the study team games. The Wilcoxon test detected significant difference of the PC of the serve, of the pass, of the set, of the attack and of the defense of the championships competed by the study team. The Kruskal Wallis Anova detected significant difference of the PC of the set (H 11 = 182,6, p = 0,0001) and of the attack (H 11 = 60,05, p = 0,0001) of the court zone. The Kruskal Wallis Anova detected significant difference of the PC of the pass (H 5 = 32,43, p = 0,0001), of the set (H 5 = 71,28, p = 0,0001) and of the attack H 5 = 33,92, p = 0,0001) of accordance with the player position. In conclusion, the match analysis after the game is an important task that helps the coach prescribe the training based on the results of the competition with the objective of improves the competitive performance of the volleyball team for the competition.